THE CHANGE OF VIETNAMESE FOLK BELIEFS IN THE NEW CONTEXT: STUDY A TYPICAL RELIGIOUS ACTIVITY (Isagoge - Journal of Humanities and Social Sciences, 2021)
Vietnam is a multi-faith and multi-religious country. According to incomplete statistics, Vietnam has about 95% of the population with religious and religious life. Up to now, the country has about 45,000 belief establishments, of which there are more than 2,900 relics associated with belief and religious establishments. Religious activities take place vibrantly throughout the country; many major religious activities and activities were solemnly organized, attracting hundreds of thousands of attendees. However, in recent years, many religious activities have changed in both positive and negative directions. This study selects a popular folk belief activity of the Vietnamese people, the funeral rite. Based on the survey, this study focuses on analyzing the actual situation of funeral rites, the values ​​, and limitations of this religious activity.